TI_GERICHTE 60.2004.436 vom 7. Februar 2005 , ricorso contro l'atto di accusa (le censure sollevate sono pertinenti al merito). - TI Tribunale d'appello (2005)
ricorso contro l'atto di accusa (le censure sollevate sono pertinenti al merito).